PENGARUH PENGELOLAAN KELAS TERHADAP HASIL BELAJAR PESERATA DIDIK PADA PEMBELAJARAN IPS KELAS VIII SMPN 7 SUNGAI AMBAWANG - Dahlan, Muhammad; Aminuyati, Aminuyati; Khosmas, F. Y. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis study aims to determine the magnitude of "The Influence of Class Management on Student Learning Outcomes in Social Studies Learning Class VIII SMPN 7 Sungai Ambawang". This study uses a quantitative approach in the form of correlation research. The research population was all students of class VIII SMPN 7 Sungai Ambawang, namely 40 students and the samples taken in this study were 40 students. The variables studied were Class Management (X) with Social Studies Learning Outcomes (Y). The method used in this research is descriptive in the form of quantitative methods, namely systematically describing the influence of class management on social studies learning outcomes for class VIII students. The sample in this study was the entire population of class VIII SMPN 7 Sungai Ambawang, totaling 40 students. The results showed that the t-count is 5.144 that there is a positive and significant influence between classroom management on student learning outcomes in social studies learning class VIII SMPN 7 Sungai Ambawang through simple linear regression obtained Y = 59.235 + 0.260 X. which means the constant value is 59.235. While the value of the regression coefficient of the class management variable is positive at 0.260. How big is the percentage of the influence of classroom management on learning outcomes based on the coefficient of determination R square 0.410, or 41% while the remaining 59% is influenced by other variables. The results of the study can be concluded that there is a positive and significant effect of classroom management on student learning outcomes.Keywords: Classroom Management, Social Studies Learning Outcomes